Tecnologías limpias paneles solares red de salud del oriente (2022)
The Health Network of the East E.S.E Taking into account global climate changes and the commitment of leaders around the world in relation to the reduction of the carbon footprint Reduction of the carbon footprint, I determine to take a step forward in the care of climate change and reduction of carbon footprint. That is why he decides to formulate a project for the installation of solar panels in the Carlos Holmes Trujillo hospital and six (6) health centers with the highest influx of users and at the same time with the highest energy consumption, this in order to reduce the carbon footprint. and incidentally, as a positive consequence, give financial relief to payments for energy consumption, which will have a reduction of approximately 35%. in energy consumption. It is important for every company to have a financial balance regardless of the reason for being or the economic activity of each company. For company administrators, one of the most important points is to have a company that meets the needs of the client but also has financial profits, which is why this work not only emphasizes a great contribution to climate change but also has a reduction in the payment of public services. This project is aimed at reducing the payment of the energy bill by 30% or 35% each month, with which there will be significant financial savings and improve cash flow and have a greater projection